Уральские сказы - Бажов Павел Петрович (Внеклассное чтение, 2015)
Экземпляры: аб. (20211014) / Инвентарный номер: 61203 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 16 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4